Community Economic Development Prospect Based on Wakaf Funds - Ida Martinelli; Asliani Harahap; Zainuddin Zainuddin (Budapest International Research and Critics University, 2019)
Wakaf is a philanthropic institution that is quite old in Islamic history. The purpose of the existence of wakaf is not only just taqarrub to Allah SWT, but also gives the economic impact of wakaf objects. Wakaf is one of the solutions given by Allah to eliminate the gap between rich and poor people. Indeed wakaf has a very high economic potential in the welfare of the people. Through cash wakaf or wakaf cash investment in wakaf property in the form of plantations and others indicates that Islam does not leave its people in poverty. Based on this, the wakaf should no longer be oriented towards mosques, madrassah, burial ground, but rather towards a more productive direction producing new economic resources intended for the welfare of the people.